Peran Modernisasi Zakat dan Wakaf dalam Ekonomi Pembangunan Syariah: Kajian Literatur - Nasihin, Fikri Zainun (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2025)
Zakat and waqf, as pillars of Islamic philanthropy, play a strategic role in the sharia development economy to address poverty, inequality, and environmental crises. This article examines the modernization of zakat and waqf through digital technology, corporate waqf, and green investment, based on a systematic literature review of the journal Zakat and Waqf: Developmental Role of Modern Approaches to Islamic Philanthropy and Endowments by Abdulquadri and Quadri (2025). The findings show that digital platforms such as MyZakat in Malaysia increase zakat collection by 19.8% (MYR 7.92 billion in 2024), while Indonesia's green waqf reduces carbon emissions by 1.92 million tons of CO2 through reforestation of 9,215 hectares by 2023. Sukuk waqf in Qatar and the UAE fund education and health infrastructure, serving millions of beneficiaries. However, challenges such as low digital literacy (22.3% internet access in Sub-Saharan Africa), regulatory inconsistencies, and cyber risks (five data breach incidents by 2024) hinder its full potential. This article recommends global regulatory harmonization, increased digital literacy, and integration of artificial intelligence to optimize zakat and waqf, support maqasid shariah (hifz al-mal, hifz al-aql, hifz al-nafs) and build an inclusive civil society.